A 3-in-1 multifunctional porous organic polyimide: detection, capture and controlled release of antibacterial drugs - Diab, Rasha (2025)
Two imide-linked porous organic polymers (POPs), PI-POP and NI-POP, were synthesized and evaluated as multifunctional materials for chemical sensing, adsorption, and temperature-responsive release applications. Characterization revealed hierarchical porosity, with surface areas of 723 m2 g−1 for PI-POP and 385 m2 g−1 for NI-POP. Their π-rich frameworks enabled strong fluorescence-based detection of tetracycline (TC) as a probe molecule. PI-POP showed stronger quenching behavior, aligning with the Lehrer model, while NI-POP followed Stern–Volmer dynamics. Beyond sensing, the adsorption behavior of tetracycline was systematically investigated under various conditions, including pH, initial drug concentration, adsorbent dose, and contact time. Optimal removal was observed under neutral pH, with PI-POP achieving ∼90% TC removal at a solid–liquid ratio of 1.5. The higher surface area and pore volume of PI-POP explain its superior uptake capacity and promote it as a more effective adsorbent. Both polymers followed the Elovich model in kinetic studies and aligned with Freundlich (PI-POP) and Temkin (NI-POP) models in isothermal analysis. Comparable removal efficiencies in tap water and buffered systems confirmed their robustness and practical applicability. Furthermore, controlled release tests at physiological temperature showed faster TC release from NI-POP, likely due to weaker host–guest interactions, making it suitable for short-term delivery applications. The released TC exhibited a clear inhibition zone against both E. coli and S. epidermidis. This confirms the retained antibacterial activity and structural integrity of TC post-release. This work highlights the potential of tailored POPs for integrated environmental and biomedical applications.